Extensive Invasive Extramammary Paget Disease Evaluated by F-18 FDG PET/CT. Issue 3 (January 2015) - Li, Zu-Gui; Qin, Xiao-Jing; Sinha., Partha
<x xml:space="preserve">Abstract</x> Abstract Extramammary Paget disease (EMPD) is a rare cutaneous, intraepithelial adenocarcinoma. Because of its rarity, little is known about the value of fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) in evaluating this disease. Our case report aims to increase current knowledge of FDG PET/CT in EMPD as a noninvasive imaging tool for assessing the extension of the disease and detecting distant metastases. We reported a 64-year-old Chinese man who presented with a slowly progressive, ill-margined erythematous lesion with a crusted, eroded, and scaly surface involving multiple sites of penis, scrotum, left pelvic wall, hip, groin, and thigh for >4 years, which became extensive in the past 1 year. He was referred for an FDG PET/CT examination to further evaluate the lesions. A following skin biopsy was performed to obtain a definitive histological diagnosis. FDG PET/CT imaging revealed mild FDG uptake at the extensive cutaneous lesion with subcutaneous invasion, involvement of lymph nodes, and multiple intense FDG-avid of skeletal metastases. According to the appearance of FDG PET/CT, a provisional diagnosis of advanced cutaneous malignancy was made. Histopathology findings indicated characteristic of EMPD. The patient was treated with radiation therapy and died from complications 2 months after the last dose of radiotherapy. Our case highlighted that a whole-body FDG PET/CT should be incorporated into the diagnostic algorithm of EMPD to give a comprehensive assessment of this disease.